Provincial dances theatre: From a local project to a flagship of contemporary choreography in 35 years - Natalia V. Kuryumova (Управление культурой)
The article is devoted to the consideration of the phenomenon of the domestic dance theater, which appeared in Russia in the early 1990s, and one of the iconic representatives of which is the Yekaterinburg troupe "Provincial Dances". The goal is an attempt to periodize the 35-year creativity of the troupe and the inextricably linked creativity of the choreographer Tatyana Baganova. The periodization is based on mixed criteria. On the one hand, the connection of each chronological period with certain organizational changes, on the other - their connection with certain artistic and stylistic shifts in the creativity of the troupe and choreographer. The following methods were used: empirical observation (the author is familiar with the work of the troupe almost from the moment of its foundation); work with scientific literature and the press about the theater; interviews; semantic analysis of performances. In the history of the development of "Provincial Dances" 5 chronological periods are distinguished: 1) the initial, associated with the aesthetics of modernist theater and neo-avant-garde art, with the management of the theater by director Lev Shulman; 2) the period of self-determination and movement towards a postmodern dance performance and dual creative leadership; 3) recognition of the troupe in Russia and abroad as the flagship of Russian dance theater, the creation of the "golden" repertoire of "Provincial Dances" by Tatyana Baganova; 4) municipalization of the theater, the formation of new, more stable working conditions, the arrival of new management to the theater in the person of experienced show business managers; 5) a period that continues to this day (however, perhaps, with time there will be an understanding that a new one has already been formed), interaction with new generations of artists, the implementation of bright productions by domestic choreographers in the troupe, expanding the boundaries of understanding dance theater, the use of current forms of work with the psychophysics of artists. The article left undisclosed the issue of the theater's entry into the era and artistic worldview of metamodernism, which may have happened quite a long time ago. But this will be the topic of further research. The article is intended for readers interested in the development of modern dance theater in Russia. It will be useful for professionals in the field of choreography, theater studies and cultural studies, everyone interested in the evolution of artistic styles and organizational changes in creative teams. The article is relevant for managers and organizers of cultural events, since it touches upon issues of municipalization of theaters and interaction with new generations of artists, which is important for the development of the cultural industry in the regions.